Risk assessment of the use of source-segregated anaerobic digestates in GB agriculture - Longhurst, Philip J.; Chambers, B.; Gale, P.; Litterick, A.; Taylor, M.; Tompkins, D.; Tyrrel, Sean F. (Cranfield University, 2012)
This paper reports on the completion of a quantitative assessment of residual risks for PAS110 biofertilisers. The work focuses on the practical use of source-segregated biofertilisers as agricultural soil amendments to ensure the protection of crops, humans, animals and the wider environment. Risks from human and animal pathogens, organic compound contaminants and plant pests and diseases are considered. The study details the basis for calculating the potential for exposure to hazards using a source-pathway-receptor method to determine the extent to which controls are needed to ensure protection from harm. Scenarios that consider the highest plausible combination of hazards arising from AD feedstocks, process parameters, land application rates and differing crop categories are used which indicate the extent to which risks could occur. In conclusion, the work provides evidence for process and agricultural management practices to enable the safe use of these high value and low cost soil amendments.